Examining the Claims about the Relationship Between the Holocaust, and the Armenian Deportation - Murat Köylü (Atatürk Dergisi)
It has been debated whether Mustafa Kemal Atatürk was taken as a role model in the reconstruction process of Germany under the leadership of Adolf Hitler, which lost the First World War and tried to be destroyed by the heavy economic sanctions of the Treaty of Versailles. Immediately after Stefan Ihrig, who is at the center of these debates and who received his Ph.D. degree in 2014 for his doctoral dissertation "Nazi Perceptions of the New Turkey, 1919-1945", published his dissertation as a book titled "Atatürk in the Nazi Imagination" by Harvard University Press, columnists of some newspapers published in Turkey, criticized Mustafa Kemal Atatürk, who was founded in the 1920s and came to power from 1933 until the end of World War II. The book began to focus on how Atatürk and the newly established Turkish Republic were portrayed in the newspapers and speeches of politicians close to the Nazi Party, which was founded in the 1920s and remained in power from 1933 until the end of World War II. In particular, the book attempted to establish a similarity between the Armenian deportation and the Holocaust, and in order to strengthen the "so-called Armenian Genocide" allegations, some media outlets supporting the Armenian allegations began to support the book. The aim of this study is to discuss the claims of Stefan Ihrig, who tries to establish similarities between the "so-called Armenian Genocide" and the "holocaust", between Gazi Mustafa Kemal Atatürk, who fought the holiest struggle in world history for the construction of a modern nation together with the Turkish Nation, and Hitler and the Nazis, who committed the greatest genocide in world history.